If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(-g-10)+10=-10+8g
We move all terms to the left:
-3(-g-10)+10-(-10+8g)=0
We add all the numbers together, and all the variables
-3(-1g-10)-(8g-10)+10=0
We multiply parentheses
3g-(8g-10)+30+10=0
We get rid of parentheses
3g-8g+10+30+10=0
We add all the numbers together, and all the variables
-5g+50=0
We move all terms containing g to the left, all other terms to the right
-5g=-50
g=-50/-5
g=+10
| -8t-3(7t+5)=-7(3t-7) | | (5r+5)=(8r-6) | | 10+8÷y=14 | | 2.x-7=3 | | 18+3x=-30+5x | | 2(j-5)-2=2 | | -38=8x+5 | | 0.9=0.4m | | 1.5(t-6)=3 | | -6=-3(m+6) | | 5=x=-22 | | 4(9u+10)-3u=-10+8u | | x(x)=x2=16x | | -4s+4=-6(-2s+10) | | –4s+4=–6(–2s+10) | | 2(p-2)-4=4 | | 0.72x=42 | | 11y-8y-11=35.08 | | 2(r−1)+2=10 | | -6(x-17)=-60 | | r+4r=3 | | 5=x=12 | | 6.x-16=2 | | X=-40y+200 | | 4=2−(–2s) | | 4=2−–2s | | 13+4x=-6x | | y=3000(0.96)^10 | | 15=x24+32 | | 24x+7=−4x | | -6(x-19)=108 | | 13+4x=-6 |